Incisor molar hypomineralization and treatment protocols in integrated dental practice (Research, Society and Development, 2022)
Incisor molar hypomineralization (IMH) is a qualitative enamel defect that alters the maturation and calcification of permanent molars and incisors. The defects occur in a very varied way, the enamel presents itself opaque with its mineral part, microhardness, reduced elasticity modulus and lower density of hydroxyapatite. This study aims to know the main clinical characteristics, epidemiology, and the differential diagnosis of IMH as well as to identify the various protocols for treating IMH and their particularities, facilitating the understanding and conduct of the dental surgeon. This study fits the research design, descriptive literature review with integrative and qualitative-exploratory analysis based on the main research platforms, searching for the terms "Molar Incisor Hypomineralisation", "Etiology", "Histology", "Prevalence"; "Diagnosis"; "Differential diagnosis", "Treatment". Articles were included in the time interval from 2011 to 2021 in English, Portuguese and Spanish language and the search resulted in 39 articles. Therefore, it can be concluded that patients with IMH have spontaneous hypersensitivity due to exposure of dentinal tubules, enamel has a rough surface favoring plaque accumulation, affected teeth become difficult to anesthetize due to chronic stress to the pulp, atypical restorations are common in these patients as well as coronal fractures. Prevalence varies as clinical examinations are not standardized and diagnosis can be misdiagnosed. The cause of IMH is imprecise, being considered multifactorial and related to genetics, environment, systemic factors, use of medications during the period of odontogenesis. Early diagnosis and a correct prevention and treatment plan prevent the aggravations of the disease.